Pengembangan Media Pemasaran, Manajemen Keselamatan Kesehatan Kerja dan Peningkatan Kewirausahaan pada Kelompok Pengrajin Batu Besar Kota Batam - Sidabutar, Yuanita FD; Bintang, Malahayati Rusli; Raymond, Raymond (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The purpose of this PKM is to increase expertise and understanding in the field of product marketing and the use of marketing media, second, to improve occupational safety and health management skills and skills, three. To increase skills and skills through entrepreneurship assistance so as to increase the potential for business development, temporary results obtained from the implementation of community service programs. community (PKM) it can be concluded that this program has a positive impact on the economy and social groups of craftsmen.